2014
DOI: 10.1631/jzus.b1400095
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of cardiac rupture in patients with ST-elevation myocardial infarction

Abstract: Cardiac rupture (CR) is a potentially fatal mechanical complication of ST-elevation myocardial infarction (STEMI). We aimed to determine the incidence and risk factors of CR in Chinese STEMI patients. A total of 9798 consecutive STEMI patients from four centers in China were retrospectively analyzed, among which 178 patients had CR. STEMI patients without CR were chosen as a control group. Clinical characteristics were compared between STEMI patients with CR and those without CR. The incidence of CR in STEMI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
3
25
1
Order By: Relevance
“…Old age has been consistently reported as a risk factor for VFWR in many previous reports. [ 21 23 ] On the contrary, female sex did not emerge as a significant independent predictor for VFWR in our study. Several studies have shown higher incidences of VFWR in women even without thrombolytic therapy.…”
Section: Discussioncontrasting
confidence: 86%
“…Old age has been consistently reported as a risk factor for VFWR in many previous reports. [ 21 23 ] On the contrary, female sex did not emerge as a significant independent predictor for VFWR in our study. Several studies have shown higher incidences of VFWR in women even without thrombolytic therapy.…”
Section: Discussioncontrasting
confidence: 86%
“…An increase in white blood cell count (leukocytosis) is associated with increased mortality during AMI and represents an independent prognostic factor to develop HF and cardiogenic shock. 2629 The TIMI10A and TIMI10B trials involving approximately 1000 patients with STEMI (reperfused by fibrinolytic therapy) showed an independent association between leukocytosis and failure of reperfusion, thrombus resistance, incidence of HF and death. 30 A substudy of the more recent HORIZONS-AMI trial involving approximately 3000 patients with STEMI undergoing primary percutaneous coronary intervention (PCI) observed an independent association between leukocytosis, infarct size and 1 year mortality.…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…Left ventricular free-wall rupture (LVFWR) may represent a dramatic and life-threatening event, occurring in up to 2% of patients with acute myocardial infarction (AMI). 1,2 The clinical presentation varies from a catastrophic blowout type characterized by cardiogenic shock and eventually cardiac arrest, to the oozing type with haemodynamic instability and pericardial effusion. 3 Prompt diagnosis and management can lead to successful treatment for LVFWR.…”
Section: Introductionmentioning
confidence: 99%